The Effect of Service Quality and Store Attempt on Repurchase Decisions on Indomaret Salatiga Minimarket Consumers with Sales Promotions as Mediation Variables (Study on The Millenial Generation) - Pingky Dayu Veronica; Linda Kusuma (Budapest International Research and Critics University, 2022)
The growth of the business sector is currently very fast, both in the small, medium and large business sectors which indicate progress. The number of new businesses, the more competition, so companies must have good services in order to create perceptions of consumer behavior and the attractiveness of repurchase decisions. This research uses quantitative methods that can be used to examine the population or certain samples. Based on the results of hypothesis testing, it can be concluded that service quality has a significant effect on consumers repurchase decisions at the Indomaret Salatiga minimarket. The results are the same for the store atmosphere variable which has a significant effect on the consumer repurchase decision of the millennial generation at the Indomaret Salatiga minimarket.